Novel approach to create hybrid and hierarchical scaffolds aimed for tissue regeneration - Oliveira, Sara M. (2012)
Tissue Engineering scaffolds with a wide range of properties and using several types of materials have been produced using different processing techniques. Among those, hybrid scaffolds, made of synthetic biodegradable and natural-origin polysaccharides, have been arising as the most adequate 3D structures to support the mechanical solicitations once implanted as well as cell adhesion, proliferation and differentiation. A well-known methodology to combine micro/nanofibers with/ within scaffolds is the combination of electrospinning and bare scaffold. However, in the common approach, fibers are not homogeneously distributed along the 3D scaffold, being limited to its surface; to achieve deposition on the interior of the scaffold, the electrospinning has to be used during bare scaffolds preparation in a complex process that may lead to structure delamination. Herein, we present a novel approach to hybridize and introduce fibrillar structures and coatings inside 3D scaffolds, rendering truly hierarchical systems. The structures were created combining an unconventional layer-by-layer (LbL) electrostatic selfassembly technology with physical crosslinking by freeze-drying. LbL is based on a simple alternated deposition of polyanions and polycations, i.e. polyelectrolytes (PEs), and the introduction of such materials inside the scaffolds creates a new environment which allows to control cell behavior, by enhancing surface area available for cells attachment and the similarity to extracellular matrix composition and structure, without damaging the mechanical integrity and properties of the bare scaffold. Alginate and chitosan were used as polyanion and polycation, respectively, and polycaprolactone bare scaffolds were produced by rapid prototyping. Scaffolds were modified with the PEs using a homemade dipping robot to study the effect of several LbL assembling parameters on the final structure. Characterization of the structures revealed that one can obtain nanocoatings or nanocoatings plus fibrillar structures inside the scaffolds, homogeneously distributed and linked to the wall of the bare scaffold in a controlled manner. SaOs-2 osteoblastic-like cells were used to assess the cytocompatibility of the hybrid scaffolds quantifying dsDNA, ALP activity and observing cell distribution. After 7 days in culture, cells were able to colonize whole longitudinal section of the scaffolds, being able to adhere to the fibrillar structures and showing similar or higher ALP activity and dsDNA content comparing with the unmodified PCL scaffolds. In conclusion, this new methodology virtually allows the modification of any 3D structure with the introduction of a new hierarchical level in tissue engineering scaffolds, as coatings or fibrillar structures, which acts as systems to control cell adhesion, proliferation and differentiation.